Analysing the challenges in building resilient net zero carbon supply chains using influential network relationship mapping - K.E.K., Vimal; Kumar, Anil; Sunil, Siddharth Meledathu; Suresh, Gokul; Sanjeev, Navaneeth; Kandasamy, Jayakrishna (Elsevier, 2022)
Implementing net zero carbon supply chain (NZCSC) practises has become critical for organisations across the globe to achieve carbon neutrality in the wake of increasing climate change and global warming. Hence it is important to identify the challenges in the implementation of resilient NZCSC to support the stakeholders. The key thirteen challenges in the implementation of resilient NZCSC were identified from an extensive literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. and industrial experts’ opinions. The challenges were investigated and ranked based on interrelations using procedures like Influential Network Relationship Mapping i.e., Decision Making Trial and Evaluation Laboratory (DEMATEL) and Level Partitioning by Total Interpretive Structural Modelling (TISM) is utilised to understand the cause-effect relationship among the challenges and to further identify the key influential challenges. The alpha value after DEMATEL was found to be 0.11 and identified the lack of management willingness as the main barrier. Level partitioning showed that lack of carbon accounting is the most critical barrier, based on which a roadmap is developed to support the stakeholders. The results from the study can help managers of organisations to implement techniques to achieve an NZCSC. Combining DEMATEL and TISM is the main novelty of the study along with the roadmap. The key findings from the study provide important insights into achieving an NZCSC from both a strategic and policy-making point of view.